Рогачицький горизонт в степових поховальних традиціях - Спіцина, Л.А. (Археологія, 2016)
Спираючись на подібність посуду, стратиграфічної позиції та рис обряду автор аналізує групу поховальних пам’яток у Подніпров’ї, Побужжі та в степовому Криму. Discussed is a series of burials (taking into account the stratigraphic position and ritual features), dishes of which tend to the middle layer at Mykhaylivka. These funeral monuments cover the territory between the Dnipro and Southern Buh Rivers, as well as the steppe Crimea. The absolute majority of dishes from these sites are samples with a round bottom. Stratigraphic position of these graves has allowed the author to add the burials without utensils to them. Primarily, it is about burials which were part of small cemeteries with single mound, or those which demonstrate ritual similarities. Funeral ceremony was not monotonous. It is only the orientation which was constant: most of graves are oriented to the east. Such burials usually formed a large burial mounds arising on the principle of burial grounds and eventually were closed by a general mound. Central burials predominated there, other situated on the periphery, sometimes exceeding the bounds of a common embankment. The embankment’s height reached 0,8—1,6 m and the diameter was up to 10—15 m. The burials were often made in the pits of quadrangular plan shape with rounded corners, although there are also oval pits, particularly, made for stretched graves. Only two cemeteries had a permanent funeral ritual. Other ones are diverse, for instance with a combination of various poses of the dead: extended, crouched, and crumpled on the back bodies. Ochre for strewing corpses and graves was used limitedly. Such usage of ochre in the funeral ceremony indemnified for products made of it. There are few traces of animals used in the funeral ceremony. Dishes are various with domination of round-bottomed ones with spherical or elongated proportions, with a high neck and shoulders retreating without ornamentation. There are metal objects in the graves. They are usually small adornments. Flint flakes are sometimes found. In general, burial ceremony of the Late Copper Age Steppe population presents the multiplicity, while the early Yamna culture population, on the contrary, shows the ritual unity. This fact led to the appeal to the stratigraphy of barrows. It allowed the author to ascertain that the selected burials (Rohachyk horizont) occupy a stratigraphic position between the oldest Copper Age burials and the ones of Yamna culture. Рассматривается ряд погребений (с учетом стратиграфической позиции и черт обряда), посуда из которых тяготеет к среднему слою Михайловки. Территориально погребальные памятники охватывают Поднепровье и Побужье, а также степной Крым. Абсолютное большинство посуды из этих памятников составляют образцы с круглым дном. Стратиграфическая позиция этих погребений позволила присоединить к ним и захоронения без посуды. Речь идет, в первую очередь, о погребениях, входивших в состав небольших могильников с общей насыпью, или такие, которые демонстрирует обрядовое сходство. Погребальный обряд был неоднообразным. Постоянной является лишь ориентация — большинство захоронений имеют восточную ориентацию. Обычно такие погребения образовывали небольшие могильники, которые возникли по принципу грунтовых и со временем были перекрыты общей насыпью. Доминирующую позицию занимали центральные захоронения, другие расположены на периферии, иногда выходя за пределы насыпи. Высота насыпи достигали 0,8—1,6 м, диаметра 10—15 м. Захоронение чаще осуществлено в ямах четырехугольной формы с закругленными углами, хотя встречаются и овальной, в частности, для вытянутых захоронений. Только два могильника имеют подобие в погребальном обряде. Другим свойственно разнообразие, в частности сочетание различных поз погребенных — вытянуто, скорчено на боку и скорчено на спине. Охра для посыпки покойников и могилы использовалась в ограниченном количестве. Такое использование охры в погребальном обряде компенсировалось изделиями из нее. Следов использования животных в погребальном обряде обнаружено немного. Посуда разнообразна, но преобладает округлодонная шаровидной формы или удлиненных пропорций, с высокой горловиной и покатыми плечиками, без орнамента. В могилах встречаются и металлические вещи. Обычно это мелкие украшения. Иногда встречаются кремневые отщепы. В целом погребальный обряд познеэнеолитического населения Степи демонстрирует разнообразие, ранним ямникам, напротив, присуще ритуальное единство. Это обусловило обращение к курганной стратиграфии. Что позволило выяснить, что отобранные захоронения (рогачицкий горизонт) занимают стратиграфическую позицию между древнейшими энеолитическими и ямными.